Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

Unpacking Multiculturalism and Islam in Malaysia: State–Corporate Television Celebrations of Bangsa Malaysia - Khattab, Umi (Television Histories in Asia: Issues and Contexts, 2015)
This chapter presents a critical analysis of media and change in postcolonial Malaysia, a South-East Asian nation of 29  million multicultural people, with a focus on the role of television in the nation’s transformation following independence from British rule in 1957. Despite having inherited the basic democratic institutions of the British political tradition, Malaysia continues to debate the transition from soft authoritarianism to democracy (Means 1996 :  103). Since 1957, Malaysia has been led by a single political party, the Barisan Nasional (BN). While the BN is a coalition of three major ethnic-based political groups, the United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA) and the Malaysian Indian Congress (MIC), it is, in effect, a symbol of Malay-Muslim supremacy (Ketuanan Melayu). UMNO, the dominant group within the party, has, since its formation, aspired to uphold Malay culture as national culture and Islam as the offi cial religion for the country. From the fi rst general elections in 1959 until the 2008 general elections, the BN held two-thirds of the 222 seats in the Dewan Rakyat (House of Representatives). Malaysian media scholar Karthigesu ( 1987 , 1994 ) contends this was largely due to the role of public television, which was launched and promoted by government itself, broadcasting in its colonial service model. In fact, the arrival of state television in 1963 coincided with the formation of the Federation of Malaysia (Moten and Mokhtar 2013 ). In this chapter I argue that television has been pivotal in shaping and transforming the political and cultural landscape of Malaysia as the medium evolved from a strictly national to a loosely global and then fluidly trans-local orientation. While television fi rst enabled the BN to hold its two-thirds majority and build the nation premised on Malay supremacy policies, it subsequently played a part in weakening the BN’s grip over the multiethnic electorate as the UMNO Ketuanan Melayu ideology, layered deep beneath the powdered face of television, surfaced in the digital media era.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Malaisie (corpus analysé); _Nettoyé

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Black, White, and in Color: Television and Black Civil Rights - Torres, Sasha (Princeton University Press, 2018)
This book examines the representation of blackness on television at the height of the southern civil rights movement and again in the aftermath of the Reagan-Bush years. In the process, it looks carefully at how television's ideological projects with respect to race have supported or conflicted with the industry's incentive to maximize profits or consolidate power. Sasha Torres examines the complex relations between the television industry and the civil rights movement as a knot of overlapping interests. She argues that television coverage of the civil rights movement during 1955-1965 encouraged viewers to identify with black protestors and against white police, including such infamous villains as Birmingham's Bull Connor and Selma's Jim Clark. Torres then argues that television of the 1990s encouraged viewers to identify with police against putatively criminal blacks, even in its dramatizations of police brutality. Torres's pioneering analysis makes distinctive contributions to its fields. It challenges television scholars to consider the historical centrality of race to the constitution of the medium's genres, visual conventions, and industrial structures. And it displaces the analytical focus on stereotypes that has hamstrung assessments of television's depiction of African Americans, concentrating instead on the ways in which African Americans and their political collectives have actively shaped that depiction to advance civil rights causes. This book also challenges African American studies to pay closer and better attention to television's ongoing role in the organization and disorganization of U.S. racial politics.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Regular Television Put to Shame by Negro Production”: Picturing a Black World on Black Journal - Heitner, Devorah (Watching While Black, 2012)
In the first episode of Black Journal , before the opening credits, comedian Godfrey Cambridge appears dressed in overalls and a painter’s cap with a paint roller in hand and methodically paints the television frame. To the viewer, it appears that his or her television is being painted black from the inside—a potent visual symbol from the first national Black public affairs program. Initially, though, the symbol emphasizes a visual challenge to the absence of Black faces on television—a show that “looks” Black, because of the visibility of its Black hosts and reporters, but where whites still have significant
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Interpreting Cubanness, Americanness, and the Sitcom: WPBT-PBS’s ¿Qué pasa U.S.A.? (1975–1980) - Rivero, Yeidy M. (Global Television Formats: Understanding Television Across Borders, 2012)
I was about 10 or 11 years old when I, together with my parents, religiously tuned in weekly to the situation comedy ¿Qué pasa U.S.A.? While I do not recall the speciﬁc year the show aired in Puerto Rico, I do remember that it was broadcast on WIPR-Channel 6, the island’s public television station. Watching one of my favorite sitcoms on what I then considered the boring channel was rather odd. However, I never thought it strange that the Peñas, ¿Qué pasa U.S.A.? ’s working-class three-generation Cuban/Cuban-American family, resided in Miami or that some of the characters communicated bilingually in English and Spanish. For me, ¿Qué pasa U.S.A.? was a show that resembled other locally produced situation comedies broadcast on commercial television, with the difference that the Peña family were Cuban immigrants who, instead of residing in Puerto Rico (like some of my childhood friends), lived in Miami (like many of my friends’ relatives). Probably as a result of the principal characters’ cultural references and their accents in Spanish, I decoded ¿Qué pasa U.S.A.? as a Cuban sitcom. Fast-forward to 2004. I was invited to write a 500-word encyclopedia entry on ¿Qué pasa U.S.A.? Without having any information on the show at hand, I immediately accepted. This was an opportunity to revisit a program I loved. After conducting the research I realized the uniqueness of ¿Qué pasa U.S.A.? Sponsored by the U.S. Ofﬁce of Education Emergency School Assistance Act– Television Program (ESAA-TV), ¿Qué pasa U.S.A.? —considered the ﬁrst bilingual situation comedy broadcast on U.S. television— addressed the culturalgenerational misunderstandings and the socio-cultural adjustments endured by the Peñas, a 1960 Cuban exile family.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Cuba (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)